The Role of ESL in Bilingual Programs A Clarification - Schinke, Linda ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
The field of ESL in recent years has drawn much criticism from bilingual educators. This criticism is related to three areas: the former use of ESL in Americanization programs, the role of ESL in legislation providing for transitional bilingual programs, and the failure of the ESL component in certain bilingual programs, due either to the teacher, student, or evaluator factor. Certain recommendations can be made to improve the three areas mentioned. Through individual as well as group effort, pressure can be brought to bear upon school boards and state and federal legislatures to view ESL as the tool to make children bilingual, not as the tool to convert them to monolingual English speakers. In addition, improvements in preparation of evaluators and teachers can be made. Since ESL is part of bilingual education, the progress of bilingual education as a whole depends on the quality of each of its parts. (Author)
ERIC Note: Paper presented at the Annual International Bilingual-Bicultural Education Conference (5th, San Antonio, Texas, April 30-May 5, 1976) and at the Interdisciplinary Linguistics Conference (University of Louisville, Kentucky, May 6-8, 1976).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingual Education; Educational Assessment; Educational Objectives; English (Second Language); Language Instruction; Language of Instruction; Language Programs; Second Language Learning; Teacher Education; Teaching Methods; Speeches/Meeting Papers